2016
DOI: 10.1128/jvi.02964-15
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Protein NP1 of Human Bocavirus 1 Plays a Critical Role in the Expression of Viral Capsid Proteins

Abstract: A novel chimeric parvoviral vector, rAAV2/HBoV1, in which the recombinant adeno-associated virus 2 (rAAV2) genome is pseudopackaged by the human bocavirus 1 (HBoV1) capsid, has been shown to be highly efficient in gene delivery to human airway epithelia (Z. Yan et al., Mol Ther 21:2181-2194, 2013, http://dx.doi.org/10.1038/mt.2013.92). In this vector production system, we used an HBoV1 packaging plasmid, pHBoV1NSCap, that harbors HBoV1 nonstructural protein (NS) and capsid protein (Cap) genes. In order to simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
103
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 31 publications
4
103
2
Order By: Relevance
“…1B and C) but not with those that end at or before nt 5200 (26), and that it is present only in total RNA and not in mRNA samples (34), we speculated that this transcript was encoded by HBoV1 sequence encompassed by the fragment from nt 5124 to 5395 and not a spliced form of the viral polyadenylated mRNA. To identify the exact ends of the BocaSR, we performed both 5= and 3= rapid amplification of cDNA ends (RACE) (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…1B and C) but not with those that end at or before nt 5200 (26), and that it is present only in total RNA and not in mRNA samples (34), we speculated that this transcript was encoded by HBoV1 sequence encompassed by the fragment from nt 5124 to 5395 and not a spliced form of the viral polyadenylated mRNA. To identify the exact ends of the BocaSR, we performed both 5= and 3= rapid amplification of cDNA ends (RACE) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…1A, in which a negative-sense genome (ϪssDNA) of HBoV1 is diagrammed. We also analyzed VP- encoding mRNA transcripts in total RNA isolated from pCMVNS*Cap-transfected HEK293 cells, using a Cap2 probe spanning nt 3921 to 5200 and an NSCap2 probe spanning nt 542 to 5124 (26). These analyses revealed that transfection with the HBoV1 duplex genome produces NS-, NP1-, and VP-encoding mRNAs (26,34) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NP1 plays important roles not only in the replication of bocaparvovirus DNA (22,30) but also in the processing of the viral pre-mRNA (31)(32)(33). It is essential to generate the mRNA that encodes viral capsid proteins VP1, VP2, and VP3 (33). HBoV1 NP1 colocalizes within the autonomous parvovirus-associated replication (APAR) bodies and complements the function of the minute virus of mice (MVM) NS2 protein in viral DNA replication during the early phase of infection (34).…”
Section: Importancementioning
confidence: 99%
“…NP1 plays important roles not only in the replication of bocaparvovirus DNA (22,30) but also in the processing of the viral pre-mRNA (31)(32)(33). It is essential to generate the mRNA that encodes viral capsid proteins VP1, VP2, and VP3 (33).…”
Section: Importancementioning
confidence: 99%